FMCG brands’ use of Facebook: an exploratory content analysis of branded entertainment - Ye, Zi-Xia (2018)
The effectiveness of traditional advertising is decreasing. With the emergence of the Internet and the increasing use of social networking sites, individuals and corporations tend to now communicate with others through social platforms. Corporations also conduct marketing strategies on social networking sites such as Facebook brand profile pages. Branded entertainment, as an upgraded form of product placement, is able to promote brands or products in a less offensive and more effective way. In this scenario, there is an integration of advertising and entertainment, which promotes products and brands as well as entertaining users at the same time. Branded entertainment is considered as a communication tool, especially when it is utilized on social networking websites. Brands can present their branded content on brand pages and users are able to comment and give their opinion on the posts. Equally, brands can also interact with users and subsequently build connections with users. Previous studies also show that branded entertainment has become an increasingly popular marketing ploy for marketers; there are over 60 million active brand profile pages conducting this form of marketing on Facebook. According to Hudson and Hudson (2006) and Zhang et al. (2010), the Fast-Moving-Consumer-Goods (FMCG) industry is keen on adopting branded entertainment. The purpose of this study is to examine features of branded entertainment presented on Facebook brand profile pages in the FMCG industry based on the conceptual framework of play theory. The research aims to answer questions including (1) which types of branded entertainment are more prevalent on FMCG brands’ Facebook profile pages and (2) how branded entertainment on FMCG brands’ Facebook profile pages utilize different play themes. Content analysis was used to analyze 362 posts on Facebook brand profile pages in the time period from July 1st 2017 to June 30th 2018. The sample of this research comprised four selected FMCG brands: Coca Cola, L’Oréal, Lay’s and M.A.C. The findings of the research show that over 50% of FMCG posts did not constitute branded entertainment. These posts were named photos/advertisement in this study as these posts directly promoted products or brands without elements of entertainment. The most frequently used branded entertainment type is festivals/carnivals/events, while the least used branded entertainment type in FMCG brands Facebook profile pages is downloads/Facebook applications. In terms of the use of play theory, play as frivolity is the predominant used play theme, which is consistent with previous research. This play theme was frequently incorporated with online interactive games/word play. The least utilized play theme was play as fantasy. Overall, there are limited types of branded entertainment used by FMCG brands on their Facebook pages. By utilizing branded entertainment and play theory, FMCG brands are able to motivate users to both engage in the activities and build connection with users. Notably, the most frequently attended festivals/carnivals/events might enable FMCG brands to generate word-of-mouth advertising on Facebook and achieve an increase in brand awareness. As no previous research has explored the use of branded entertainment on FMCG brands’ Facebook profile pages, this study fills the gap in the literature and also provides practical suggestions of the use of branded entertainment to FMCG marketers.